2020
DOI: 10.1097/j.pain.0000000000001969
|View full text |Cite
|
Sign up to set email alerts
|

Are endogenous opioid mechanisms involved in the effects of aerobic exercise training on chronic low back pain? A randomized controlled trial

Abstract: Aerobic exercise is believed to be an effective chronic low back pain (CLBP) intervention, although its mechanisms remain largely untested. This study evaluated whether endogenous opioid (EO) mechanisms contributed to the analgesic effects of an aerobic exercise intervention for CLBP. Individuals with CLBP were randomized to a 6-week, 18-session aerobic exercise intervention (n = 38) or usual activity control (n = 44). Before and after the intervention, participants underwent separate laboratory sessions to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…The characteristics of the included studies are reported in Table 2 . Of the 11 included studies, seven studies had an experimental, repeated measures design [ 33 , 37 , 41 , 45 48 ] and four were randomised controlled trials [ 49 52 ]. Five studies recruited individuals with chronic low back pain [ 33 , 37 , 47 , 48 , 52 ], three studies examined those with chronic musculoskeletal pain [ 33 , 37 , 45 , 46 , 51 ], two investigated individuals with neck pain [ 49 , 50 ], and one included individuals with knee pain due to OA [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included studies are reported in Table 2 . Of the 11 included studies, seven studies had an experimental, repeated measures design [ 33 , 37 , 41 , 45 48 ] and four were randomised controlled trials [ 49 52 ]. Five studies recruited individuals with chronic low back pain [ 33 , 37 , 47 , 48 , 52 ], three studies examined those with chronic musculoskeletal pain [ 33 , 37 , 45 , 46 , 51 ], two investigated individuals with neck pain [ 49 , 50 ], and one included individuals with knee pain due to OA [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 included studies, seven studies had an experimental, repeated measures design [ 33 , 37 , 41 , 45 48 ] and four were randomised controlled trials [ 49 52 ]. Five studies recruited individuals with chronic low back pain [ 33 , 37 , 47 , 48 , 52 ], three studies examined those with chronic musculoskeletal pain [ 33 , 37 , 45 , 46 , 51 ], two investigated individuals with neck pain [ 49 , 50 ], and one included individuals with knee pain due to OA [ 41 ]. Four studies were conducted in Denmark [ 45 47 , 50 ], two studies were undertaken in the United States of America [ 37 , 52 ], and the remaining studies were conducted in Belgium [ 33 ], Ireland [ 41 ], Turkey [ 51 ], Spain [ 48 ] and Poland [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SREP sensitization might be useful in the discrimination of bottom-up versus top-down CS processes, and this could be useful clinically in the context of individualized treatment. Thus, if SREP primarily reflects top-down CS mechanisms, patients with greater SREP sensitization may obtain greater benefit from therapies that may enhance descending inhibition, such as physical exercise, psychological interventions, and medications enhancing neurotransmitters involved in pain inhibition (e.g., selective norepinephrine reuptake inhibitors (SNRIs) 6,79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on a systematic review of the exercises that can be performed after rehabilitation, no exercises have been contraindicated, and multiple practical modalities can be proposed to the patients [40]. The effectiveness of physical activity is probably linked not only to a change in muscular strength but also to other mechanisms such as endogenous opioid mechanisms [41], mood improvement, reduction of kinesophobia, and cortical reorganisation [42].…”
Section: P a G E 8 | 51mentioning
confidence: 99%